An invasive herbivore structures plant competitive dynamics. (29th November 2017) - Wong, Lydia; Grainger, Tess Nahanni; Start, Denon; Gilbert, Benjamin
Abstract : Species interactions are central to our understanding of ecological communities, but may change rapidly with the introduction of invasive species. Invasive species can alter species interactions and community dynamics directly by having larger detrimental effects on some species than others, or indirectly by changing the ways in which native species compete among themselves. We tested the direct and indirect effects of an invasive aphid herbivore on a native aphid species and two host milkweed species. The invasive aphid caused a 10-fold decrease in native aphid populations, and a 30% increase in plant mortality (direct effects). The invasive aphid also increased the strength of interspecific competition between the two native plant hosts (indirect effects). By investigating the role that indirect effects play in shaping species interactions in native communities, our study highlights an understudied component of species invasions.